2019
DOI: 10.1017/jsi.2018.20
|View full text |Cite
|
Sign up to set email alerts
|

Combating Special Educator Attrition: Mentor Teachers’ Perceptions of Job Satisfaction, Resiliency, and Retention

Abstract: Special educator attrition is a major problem in the United States (US) and in many countries worldwide. In the present study, we investigated the experiences of 5 highly successful special education teachers serving students with autism spectrum disorder in the central Florida area of the US with particular attention to factors associated with teacher retention. A phenomenological research design was employed to identify factors leading participants to persevere where others have not. A representative sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…They argue that having more children with ASD in a class can lead to educator burn out despite educator's having the knowledge and skills to work with children with ASD. Mrstik et al ( 47 ) reported that retention of educators of children with ASD in the special education sector was a major problem in the United States as well as other countries around the world resulting in a shortage of special educators. In a phenomenological study on the lived experience of educating students with ASD, educators reported that high workloads coupled with poor support from administrators was a major source of stress in educators ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…They argue that having more children with ASD in a class can lead to educator burn out despite educator's having the knowledge and skills to work with children with ASD. Mrstik et al ( 47 ) reported that retention of educators of children with ASD in the special education sector was a major problem in the United States as well as other countries around the world resulting in a shortage of special educators. In a phenomenological study on the lived experience of educating students with ASD, educators reported that high workloads coupled with poor support from administrators was a major source of stress in educators ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wald et al (2006) maintained that resilience refers to the positive adaptation and the ability to maintain or regain mental health, despite experiencing adversity. In education, the concept of resiliency has also been explored by education scholars and practitioners (see Mrstik et al, 2019;Entesari et al, 2020;Ratanasiripong et al, 2020) to describe how teachers or the curriculum adapt to and caters to the changing landscape, needs, and requirements of society. In the present study, although teachers did not have experience in conducting online and remote classes, they remained patient, flexible, and adaptive to the current teaching state of emergency remote teaching due to the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies can inform other teachers, policy-makers, and school administrators to develop strategies and policies that benefit teachers and the schools. Although there has been a number of studies that examined teachers' resiliency (see Mrstik et al, 2019;Entesari et al, 2020;Ratanasiripong et al, 2020), studies that examined how teachers perceived pedagogical resilience, and how teachers build resilience in pedagogy during the COVID-19 pandemic are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Resilience is “the process and outcome of successfully adapting to difficult or challenging life experiences, especially through mental, emotional, and behavioral flexibility and adjustment to external and internal demands” (American Psychological Association, n.d.). Therefore, educator resilience refers to the capacity of teachers and other education professionals to persist in their practice in the face of challenges, stress, and adversity in their work environment (Mrstik et al, 2019). It encompasses their ability to maintain their well-being, manage their emotions, and sustain their motivation and effectiveness as educators (Nagy, 2017).…”
Section: Educator Resiliencementioning
confidence: 99%
“…It encompasses their ability to maintain their well-being, manage their emotions, and sustain their motivation and effectiveness as educators (Nagy, 2017). Educators face various sources of stress and pressure in their work, including heavy workloads, time constraints, student behavior issues, administrative demands, and changes in educational policies or practices (Mrstik et al, 2019). These factors can significantly impact their mental and emotional well-being, job satisfaction, and overall effectiveness as teachers (Nagy, 2017; Schonert-Reichl, 2017; Shen et al, 2015).…”
Section: Educator Resiliencementioning
confidence: 99%